The Association between Monocyte-derived Macrophages TNF-a Expression and Anthropometrics Measures in Polycystic Ovary Syndrome - Naylah Muna; Oki Riayati; Heri Wibowo; Andon Hestiantoro (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Polycystic ovary syndrome (PCOS) is a female infertility disease that is often associated with low-grade chronic inflammation. This inflammation was suspected to correlate with certain body conditions, especially physical lipid composition that can be obtained under anthropometrics measurements. Monocytes and macrophages of PCOS patients were more susceptible to inflammation and contributed to this condition. Tumor Necrosis Factor-alpha (TNF-a), as one of the major inflammatory cytokines, holds an important role in the chronic inflammation of PCOS. AIMS:  This study aimed to evaluate the association of inflammatory cellular levels TNF-a in macrophage cells of women diagnosed with PCOS with physical anthropometrics. METHOD: Twenty PCOS women and ten healthy women as the control group were recruited in this study. Anthropometric data were measured. Peripheral blood was collected, mononuclear cells were isolated, and then cultured. Monocytes were selected and differentiated into macrophages. Macrophages were then exposed to oxidized Low-Density Lipoprotein (ox-LDL) and underwent flow cytometry to examine the level of TNF-a. Anthropometric data and TNF-a level were analyzed using Spearman-Rho Correlation test followed by a linear regression test. RESULT: TNF-a expression was found to be statistically correlated with Body Mass Index (BMI), waist circumference (WC), waist-to-height ratio, visceral fat level, and muscle mass of arm (MMA) (p<0.05). However, only WC and MMA gave significant impact to macrophage TNF-a expression based on linear regression association test with equation -96.971 + 0.601*waist circumference + 2.665*MMA. CONCLUSION: TNF-a was strongly associated with waist circumference and muscle mass percentage of arm in PCOS cases.